The three box solution : a strategy for leading innovation - Govindarajan, Vijay (Boston Harvard Business Review Press, 2016)
"Leaders already know that innovation calls for a different set of activities, skills, methods, metrics, mind-sets, and leadership approaches-it is well-understood that creating a new business and optimizing an already existing one are two fundamentally different management challenges. The real problem for leaders is doing both, simultaneously. How do you meet the performance requirements of the current business-one that is still thriving-while dramatically reinventing it? How do you foresee a change in your current model before a crisis forces you to abandon it? Vijay Govindarajan expands the leader's innovation toolkit with a simple and proven method for allocating the organization's energy, time, and resources-in balanced measure-across what he calls "the three boxes": • Box 1: The present-Keep the current business going • Box 2: The past-Forget what made the business successful in the past • Box 3: The future-Create the new model The "three box" framework makes leading innovation easier because it gives leaders a simple vocabulary and set of tools for managing and measuring the different sets of behaviors and activities, across all levels of the organization. Supported with rich company examples-such as Mahindra & Mahindra, Hasbro, IBM, United Rentals, Dunnhumby, Nucor, and Tata-and testimonies of leaders who have successfully used this framework to lead innovation, this book solves once and for all the practical dilemma of how to align an organization on the critical but competing demands of innovation. "--
"Leaders already know that innovation calls for a different set of activities, skills, methods, metrics, mind-sets, and leadership approaches--it is well-understood that creating a new business and optimizing an already existing one are two fundamentally different management challenges. The real problem for leaders is doing both, simultaneously. How do you meet the performance requirements of the current business--one that is still thriving--while dramatically reinventing it? How do you foresee a change in your current model before a crisis forces you to abandon it? Vijay Govindarajan expands the leader's innovation toolkit with a simple and proven method for allocating the organization's energy, time, and resources--in balanced measure--across what he calls "the three boxes": - Box 1: The present--Keep the current business going - Box 2: The past--Forget what made the business successful in the past - Box 3: The future--Create the new model The "three box" framework makes leading innovation easier because it gives leaders a simple vocabulary and set of tools for managing and measuring the different sets of behaviors and activities, across all levels of the organization. Supported with rich company examples--such as Mahindra & Mahindra, Hasbro, IBM, United Rentals, Dunnhumby, Nucor, and Tata--and testimonies of leaders who have successfully used this framework to lead innovation, this book solves once and for all the practical dilemma of how to align an organization on the critical but competing demands of innovation"--
Includes bibliographical references and index.
Keywords: Leadership; Strategic planning; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership